2022
DOI: 10.1039/d2fo00526c
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial glycemic and circulating SCFA concentrations following okara- and biovalorized okara-containing biscuit consumption in middle-aged and older adults: a crossover randomized controlled trial

Abstract: Okara is a high-fiber food by-product that can be biotransformed with Rhizopus oligosporus to improve its nutrition and palatability. This research aims to assess postprandial changes in glycemic-related and lipid-related...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Nevertheless, a recent study found that there was no difference in PPGR among healthy subjects who consumed either 100 g of 40% autoclaved or RO fermented okara-substituted biscuits, which is also a dietary fibre-rich food by-product, compared to those who consumed 100 g of control biscuits [ 41 ]. The difference in findings may be caused by the different health conditions of the subjects involved in each study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a recent study found that there was no difference in PPGR among healthy subjects who consumed either 100 g of 40% autoclaved or RO fermented okara-substituted biscuits, which is also a dietary fibre-rich food by-product, compared to those who consumed 100 g of control biscuits [ 41 ]. The difference in findings may be caused by the different health conditions of the subjects involved in each study.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al . (2022) conducted a study to evaluate the effects of consuming cookies containing dried soybean dregs and raw soybean dregs on postprandial glucose‐related outcomes and lipid‐related outcomes in middle‐aged and older adults. The findings of the study indicated that cookies enriched with soybean dregs or plain soybean dregs demonstrated a favourable impact on post‐meal insulin response, leading to a reduction in insulin levels following ingestion.…”
Section: Application For Foodmentioning
confidence: 99%